Filum terminale transection in pediatric SCIWORA with tight filum terminale: a case series and literature review - Yang, Yue; Wang, Yanfei; Tang, Wenwen; Yu, Mengyan; Fang, Huangyi; Sheng, Hansong; Shen, Gang (Frontiers in Pediatrics, 2025)
PurposeTo investigate the role of tight filum terminale (TFT) in pediatric spinal cord injury without radiographic abnormality (SCIWORA) following low-energy trauma and to evaluate the efficacy of minimal invasive interlaminar approach (MIIA) for filum terminale transection in treating these patients. The study aims to determine whether early surgical intervention can improve neurological outcomes in this specific patient population.MethodsThis retrospective case series included four pediatric patients with SCIWORA and concurrent TFT treated at Women and Children's Hospital of Ningbo University from December 2022 to May 2024. The patients underwent MIIA for filum terminale transection. We retrospectively analyzed the medical records, clinical courses, presentations, and treatment strategies for these patients.ResultsAll patients in this case series showed evidence of TFT following low-energy trauma. All patients underwent MIIA for filum terminale transection and intraspinal canal exploration due to progressive neurological impairment. None had received steroid treatment. Postoperatively, none experienced further neurological deterioration or complications. Two patients achieved complete resolution of preoperative symptoms within three months, one showed significant neurological improvement, and one had stable neurological status without further worsening.ConclusionTFT might be the etiology of SCIWORA in children after suffering from low-energy injuries. Performing filum terminale transection as early as possible after the occurrence of SCIWORA complicated by tight filum terminale in children might be beneficial for relieving the state of spinal cord ischemia and hypoxia caused by longitudinal traction of the spinal cord as early as possible and facilitating the recovery of neurological injuries.